The Effect of Tax Planning on Company Value In Non-Financial Companies Listed on The IDX in The Period 2019-2021 - Rut Meflinda; Lorina Siregar Sudjiman (Yayasan Baru Haji Samsudin, 2024)
This study aims to determine the effect of tax planning on firm value carried out to non-financial companies on the Indonesia Stock Exchange in 2019-2021. This study uses a descriptive method as well as associations, the sample used is 23 companies that have passed the criteria by using the purpose sampling method. So, the number of data examined there are 69 data. The techniques used in this research are descriptive statistical techniques, hypothesis testing, coefficient of determination test, classical assumption test and also multiple linear regression. The results of the study reveal that there is a significant effect of tax planning on firm value in non-financial companies listed on the Indonesian stock exchange